UPAYA MENINGKATKAN KETERAMPILAN MENULIS RESENSI DENGAN MODEL STAD MODA DARING PADA PESERTA DIDIK KELAS XI DI SMA N 2 BANTUL - SRI SUDIASIH (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
This Classroom Action Research aims to: 1) describe the process of applying the online mode STAD cooperative learning model in the learning process to write reviews, 2) find out the results of learning to write reviews for students in class XI MIPA 2 SMA N 2 Bantul. This Classroom Action Research uses the online mode STAD (Student Team Achievement Division) model using six stages, namely conveying learning objectives, presenting material, forming groups, providing guidance in group learning, evaluation, and providing reinforcement and rewards. The results of this study are 1) the implementation of the STAD model in the act of learning to write reviews for students correctly with the steps of orientation, exploration, re-creation, and posting. 2) There is an increase in the results of student performance on the competence of writing reviews. Improved results can be seen from the results of student performance from cycle I to cycle II. The improvement in cycle II was assisted by the teacher including a review writing format. ABSTRAKPenelitian Tindakan Kelas ini bertujuan untuk: 1) mendeskripsikan proses penerapan model pembelajaran kooperatif STAD moda daring pada proses belajar menulis resensi, 2) mengetahui hasil pembelajaran menulis resensi pada peserta didik kelas XI MIPA 2 SMA N 2 Bantul. Penelitian Tindakan Kelas ini menggunakan model STAD (Student Team Achievement Division) moda daring dengan menggunakan enam tahapan, yaitu menyampaikan tujuan pembelajaran, menyampaikan materi, membentuk kelompok, memberikan bimbingan dalam pembelajaran kelompok, evaluasi, dan memberikan penguatan dan penghargaan. Hasil penelitian ini adalah 1) implemetasi model STAD dalam tindakan pembelajaran menulis resensi pada peserta didik secara tepat dengan langkah-langkah orientasi, eksplorasi, re-kreasi, dan memposting. 2) Adanya peningkatan hasil kinerja peserta didik pada kompetensi menulis resensi. Peningkatan hasil dapat dilihat dari hasil kinerja peserta didik mulai siklus I hingga siklus II. Peningkatan pada siklus II dibantu dengan guru menyertakan format penulisan resensi.